2006
DOI: 10.1038/sj.leu.2404366
|View full text |Cite
|
Sign up to set email alerts
|

Addition of the CD28 signaling domain to chimeric T-cell receptors enhances chimeric T-cell resistance to T regulatory cells

Abstract: T cells can be engineered to target tumor cells by transduction of tumor-specific chimeric receptors, consisting of an extracellular antigen-binding domain and an intracellular signaling domain. However, the peripheral blood of cancer patients frequently contains an increased number of T regulatory cells, which appear to inhibit immune reactivity. We have investigated the effects of T regulatory cells on chimeric T cells specific for the B-cell antigen CD19, as B-cell malignancies are attractive targets for ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 32 publications
(37 reference statements)
3
127
2
1
Order By: Relevance
“…T cells transduced with a CAR containing the CD28 signaling domain could enhance IL2 production (7), sustain T-cell proliferation (7), and resist immune suppression mediated by transforming growth factor-b (TGFb) and regulatory T cells (Treg; ref. 9). The inclusion of domains derived from the tumor necrosis factor receptor family members 4-1BB and OX40 into CARs has also been shown to enhance the cytotoxicity of CAR-transduced T cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…T cells transduced with a CAR containing the CD28 signaling domain could enhance IL2 production (7), sustain T-cell proliferation (7), and resist immune suppression mediated by transforming growth factor-b (TGFb) and regulatory T cells (Treg; ref. 9). The inclusion of domains derived from the tumor necrosis factor receptor family members 4-1BB and OX40 into CARs has also been shown to enhance the cytotoxicity of CAR-transduced T cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Second-generation CAR T-cells with CD28 as a costimulator were less sensitive to Tregs and their suppressive molecules IL10 and TGFb. 13 Such CARs have shown effective in ALL but in vivo persistence can be improved for lymphoma. 5,13 The CAR T-cells developed by the University of Pennsylvania included the 4-1BB molecule as a costimulator instead of CD28.…”
Section: Car T-cell Designmentioning
confidence: 99%
“…13 Such CARs have shown effective in ALL but in vivo persistence can be improved for lymphoma. 5,13 The CAR T-cells developed by the University of Pennsylvania included the 4-1BB molecule as a costimulator instead of CD28. This has shown to give an important survival and expansion signal to the CAR T-cells and may explain the persistent responses in their patients.…”
Section: Car T-cell Designmentioning
confidence: 99%
“…For example, several groups used diverse antibodies against human EGF receptor 2 (HER2) [58][59][60][61][62][63], which is commonly overexpressed on breast-, prostate-, kidney-cancer, and many other tumors. Other popular antigens for T-bodies are B-cell markers, such as CD19 [64][65][66] and CD20 [67][68][69], which are associated with various B-cell-derived lymphomas. Optionally, using the modularity of the chimeric receptor, the recognition unit can get access to a ligand-binding domain of a heterologous receptor (linked to the TCR signaling moiety).…”
Section: Specificity Of T-bodiesmentioning
confidence: 99%
“…Moreover, Fridmann-Morvinski et al showed that expression of the tripartite chimeric receptor but not the CD28-truncated chimeric receptor could rescue activated T-cells from antigen-induced cell death [83]. In addition, recent findings showed that a CD28-domain-containing chimeric receptor enhances the resistance of the T-body to T regulatory cells [66].…”
Section: Modulating Signaling In T-bodiesmentioning
confidence: 99%